Pengaruh Pendidikan Keberlanjutan dan Perubahan Sikap Lingkungan terhadap Tindakan Berkelanjutan Mahasiswa - Rismawati, Rismawati; DAP, Fajar; Rachman, Muh Ade (Universitas Muhammadiyah Gresik, 2023)
This research aims to investigate the role of sustainability education in shaping students' environmental attitudes and actions. By identifying the impact of sustainability education on students, this research hopes to provide in-depth insight into how education can be a key instrument in encouraging behavioral change towards sustainability. This research will explore students' perceptions of sustainability education, the extent to which their knowledge and understanding has increased, and under what circumstances they have applied this knowledge in everyday life. The population used for this research was 7th semester class A students of the Faculty of Economics and Business, Muhammadiyah University of Palopo. This study utilizes a quantitative research approach to collect and examine information. This process involves several steps, first of all, conducting a literature review to evaluate previous studies related to sustainability education, changes in environmental attitudes, and students' sustainability actions to gain an in-depth understanding of the theoretical framework that is the basis of this research. There is a relationship between sustainability education and students' sustainability actions, although the direction of the relationship is negative. The practical implication of these findings is that efforts to increase changes in environmental attitudes among students can be an effective strategy in increasing sustainability behavior.